Performance evaluation of granular sub-base by maps of resistance using GrapherTM. Case study: Ibague, Colombia (2023)
In this study, we evaluated the performance of the granular sub-base materials of the "La Caima" and "Martínez" quarries located in Ibagué, Colombia, using resistance maps validated with the traditional data of optimum moisture content, maximum dry unit weight and CBR. From the results of resistance maps made for the two quarries using the Grapher software we concluded that the maximum value of CBR could be obtained with moisture values lower than the optimum moisture content. We conclude that a moisture value lower than the optimum moisture content (obtained from the Proctor test) produces higher values of CBR, for example, in the "La Caima" and "Martínez" quarries a higher CBR value is obtained when the optimum moisture content is reduced by 0.5%. In first case, CBR value increases 31.61% and the second case 24.46%. The results obtained from the two case studies indicate that the development of resistance maps is the most appropriate methodology to achieve a better compaction control of the granular sub-base materials.